2012
DOI: 10.1074/mcp.o111.016717
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Data Extraction of the MS/MS Spectra Generated by Data-independent Acquisition: A New Concept for Consistent and Accurate Proteome Analysis

Abstract: Most proteomic studies use liquid chromatography coupled to tandem mass spectrometry to identify and quantify the peptides generated by the proteolysis of a biological sample. However, with the current methods it remains challenging to rapidly, consistently, reproducibly, accurately, and sensitively detect and quantify large fractions of proteomes across multiple samples. Here we present a new strategy that systematically queries sample sets for the presence and quantity of essentially any protein of interest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
2,749
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 2,478 publications
(2,854 citation statements)
references
References 52 publications
19
2,749
1
9
Order By: Relevance
“…Sequential window acquisition of all theoretical mass spectra (SWATH MS) is a recently developed, massively parallel protein targeting technique that features high accuracy and high reproducibility in protein quantification (Gillet et al, 2012). To validate our findings, we performed SWATH MS analysis of vitreous samples from 5 iERM, 5 MH and 4 DME patients.…”
Section: Resultsmentioning
confidence: 99%
“…Sequential window acquisition of all theoretical mass spectra (SWATH MS) is a recently developed, massively parallel protein targeting technique that features high accuracy and high reproducibility in protein quantification (Gillet et al, 2012). To validate our findings, we performed SWATH MS analysis of vitreous samples from 5 iERM, 5 MH and 4 DME patients.…”
Section: Resultsmentioning
confidence: 99%
“…For SWATH-MS-based experiments the instrument (SCIEX TripleTOF 5600) was configured as described by Gillet et al [17]. Briefly, the mass spectrometer was operated in a looped product ion mode.…”
Section: Lc-swath-ms Acquisitionmentioning
confidence: 99%
“…To achieve this, SP-samples from boars with proven fertility would be examined using 1-D SDS PAGE and Nano LC-ESI-MS/MS followed by bioinformatics of Gene Ontology (GO) to evaluate cellular location, molecular function and biological process of the identified proteins. In addition, the boar SPproteome will be described so that a spectral library can be built for relative 'label free' protein quantitation with SWATH approach [17].…”
Section: Introductionmentioning
confidence: 99%
“…Using the same instrumentation as PRM‐MS, the instrument method can be adapted to allow for data independent acquisition 137, 138. Instead of coupling a quadrupole with an orbitrap mass analyzer, SWATH‐MS (sequential window acquisition of all theoretical masses) was implemented on a mass spectrometer which selects the precursors with a quadrupole and all fragment ions are analyzed by TOF 139. First clinical studies using SWATH‐MS demonstrated the usefulness of the method: Liu and colleagues concluded from the analysis of serum proteins of a longitudinal twin study that clinical serum biomarkers should be calibrated against genetic background and age adjusted 140.…”
Section: Resultsmentioning
confidence: 99%